Photocatalytic Performance of Titanates with Formula MTiO3 (M= Fe, Ni, and Co) Synthesized by Solvo-Combustion Method - Zarazúa Morín, María Elvira; Torres Martínez, Leticia Myriam; Sánchez Martínez, Daniel; Gómez Solís, Christian (Universidade Federal de São Carlos, 2017)
This work reports the synthesis of a variety of materials with an ilmenite-type structure MTiO3 formula, where M= Fe, Co, and Ni, these materials were synthesized by the method of solvo-combustion, a simple and rapid method. These materials were characterized by X-ray Diffraction (XRD), scanning electron microscopy (SEM), FT-IR spectroscopy, thermogravimetric analysis (TGA/DTA), surface area determination by the BET method and analysis of particle size. The photocatalytic activity was measured in the degradation reactions of Rhodamine B (rhB) and tetracycline (TC). The results show that the crystallinity and surface area are factors that influence significantly on the photocatalytic activity of the synthesized titanates. Keywords: Non-aqueous solution, Characterization, Titanates, solvo-combustion, organic pollutants, photocatalysis